Micro firms matter : How do they deal with the tension between production and training? - Baumeler, Carmen [Verfasser]; Lamamra, Nadia [Verfasser] (My University, 2019)
"The primary function of any firm is not to train but to produce goods and services. However, firms in collective skill formation systems, such as those in Switzerland, train apprentices in 'dual' vocational education and training programmes, where the firms become important educational actors. Generally, all training firms are coined by their context and are situated in an area of conflict between production and training. A core contextual factor is firm size, which influences the firm-specific provision of learning opportunities and pedagogical practice. Regarding providing apprenticeships in Switzerland, micro enterprises are highly important because around 40% of all apprentices are trained in firms with fewer than ten employees. Despite their importance, little is known about their everyday challenges. Therefore, we ask the following question: How do micro firms deal with the tension between production and training requirements?" (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 2.1.1 Informelles Lernen; S 3.2.1 KMU, Klein- und Mittlere Unternehmen; G 1.3.1.1 Ausbildungsstellenmarkt; I 2.2.1 Westeuropa; Betriebliche Berufsausbildung; Duales System; Lernen am Arbeitsplatz; Einflussfaktor; Betriebsgröße; Kleinbetrieb; Kleinstunternehmen; Ausbildungsverhalten; Schweiz